2006
DOI: 10.1029/2005gl025145
|View full text |Cite
|
Sign up to set email alerts
|

Crustal velocity structure across the southern Korean Peninsula from seismic refraction survey

Abstract: The first crustal‐scale controlled source seismic refraction experiment in the southern Korean Peninsula, KCRUST2002, was carried out along a 300‐km long profile across this peninsula in December 2002. Iterative processing and modeling produced a laterally varying layered crustal velocity model. The crust is thickest (34 km) below the Okcheon fold belt in the middle of the transect and thinnest (28 km) at the eastern end where the Cretaceous Gyeongsang basin is characterized by 5 km of low velocity material th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 8 publications
4
33
2
3
Order By: Relevance
“…If the shallow crustal velocity between the source and GKP1 is relatively lower than average crustal velocity of area A, the synthetic waveform from that can precede the observed one. This result is compatible with that of Cho et al (2006). They showed that the shallow crustal velocity of Gyeongsang basin is comparatively low.…”
Section: Discussionsupporting
confidence: 88%
“…If the shallow crustal velocity between the source and GKP1 is relatively lower than average crustal velocity of area A, the synthetic waveform from that can precede the observed one. This result is compatible with that of Cho et al (2006). They showed that the shallow crustal velocity of Gyeongsang basin is comparatively low.…”
Section: Discussionsupporting
confidence: 88%
“…The Moho discontinuity beneath station TJN appears at a depth of 32 km. This result is similar to the other independent works (e.g., Chang and Baag, 2005;Cho et al, 2006) in which the Moho beneath station TJN appears at 33.58 km and 32.09 km, respectively. The P-wave velocity in the upper mantle is 7.67−8.02 km/s.…”
Section: Discussionsupporting
confidence: 92%
“…The low velocity layers around a depth of 10 km are not seriously interpreted at present because they are not always distinctive and because the detailed geological structure of the Okcheon Fold Belt is expected to be very complicated by locality. The midcrustal velocity discontinuity appeared strongly at a depth of around 15 km in the WNW half portion of the KCRT2002 velocity crosssection (Cho et al, 2006). Velocity jumps at a depth of 18 km are found beneath stations NPR and TJN although the former is distinctive.…”
Section: Discussionmentioning
confidence: 91%
“…AC-16에서 정량적인 깊이는 굴절파 실험 두 측선 (Cho et al, 2006;의 7개 지점에서 속도층 모델(모델 5 지점에서 두 측선이 교차)을 구축하였는데( Fig. 1(b), (c)), 7개 모델은 측 선의 수직방향, 즉 2차원적으로 확장된 모델영역( Fig.…”
Section: 해석 방법unclassified